2020
DOI: 10.1155/2020/3208391
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Efficacy of Neoadjuvant Chemotherapy with Epirubicin and Cyclophosphamide and Weekly Paclitaxel and Trastuzumab in Human Epidermal Growth Factor Receptor 2–Positive Breast Carcinoma: A Real‐World Study

Abstract: Background. Trastuzumab has been introduced a decade ago and demonstrated improvement in the prognosis in patients with human epidermal growth factor receptor 2- (HER2-) positive (+) breast carcinoma (BC). This study is aimed at evaluating the efficacy of epirubicin/cyclophosphamide with weekly paclitaxel-trastuzumab as neoadjuvant chemotherapies in HER2+ BC patients. Methods. A total of 234 HER2+ BC patients were given neoadjuvant chemotherapy (NAC) between 2010 and 2016. The primary endpoints were pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In the neoadjuvant chemotherapy and surgical treatment of BC, an RWS study found that epirubicin/cyclophosphamide with weekly paclitaxel–trastuzumab has more advantages in both pathologic complete response (PCR) and disease-free survival (DFS) [ 37 ]. Compared with traditional anthracycline, pegylated liposomal doxorubicin (PLD) has similar efficacy, but its cardiotoxicity is significantly reduced [ 38 ].…”
Section: Breast Cancer (Bc)mentioning
confidence: 99%
“…In the neoadjuvant chemotherapy and surgical treatment of BC, an RWS study found that epirubicin/cyclophosphamide with weekly paclitaxel–trastuzumab has more advantages in both pathologic complete response (PCR) and disease-free survival (DFS) [ 37 ]. Compared with traditional anthracycline, pegylated liposomal doxorubicin (PLD) has similar efficacy, but its cardiotoxicity is significantly reduced [ 38 ].…”
Section: Breast Cancer (Bc)mentioning
confidence: 99%
“…A series of works have investigated the potential association of pCR with the long-term survival outcomes in patients with BC. An earlier randomized clinical trial revealed that pCR was correlated with prolonged disease-free survival (DFS) in BC ( 5 ). Another previous study has demonstrated that pCR in human epidermal growth factor receptor 2 (Her-2)-positive BC is associated with substantially longer times to recurrence and death ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%